Teachers' Strategies in Handling Children with Speech Delays in the Umar Group at Al Muttaqin PG - Pujarama, Dea Anggraeni; Marpuah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to describe teachers' strategies in dealing with children with speech delay disorder in the Al Muttaqin Playgroup, especially in the Umar group. Children who experience speech delay often show limited vocabulary, difficulty following simple commands, use body language more often than verbal language, and experience emotional barriers that lead to tantrum behavior. This research uses a Classroom Action Research (PTK) approach with a focus on improving learning strategies through four main stages, namely planning, implementation, observation, and reflection. The subjects of the study were several children of Umar's group who experienced speech delays. The strategies used by teachers include teacher communication strategies, environmental therapy strategies, speech therapy strategies, and compassion strategies. Data collection techniques are carried out through observation, field notes, documentation, and consultation with a team of school psychologists. The results of the study showed that there were positive developments in children, such as increased ability to pronounce new vocabulary, increased ability to express opinions, and reduced tantrum behavior due to improved communication skills. Thus, the implementation of consistent communication strategies, supported by a conducive environment and a compassionate approach, has proven to be effective in helping the language development of children with speech delays.